Pengembangan Potensi UMKM Berbasis Sumber Daya Lokal dalam Mendorong Perekonomian di Desa Margaasih Kecamatan Margaasih Kabupaten Bandung - Pebriyanti, Juwita; Syahidatulrodiahtillah; Tedjaningsih, Iis (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Community service research in Margaasih Village, Margaasih Sub‑district, Bandung Regency, aims to map and develop the potential of local resource‑based micro, small, and medium enterprises (MSMEs) through the integration of Geographic Information Systems (GIS) and participatory approaches. The 290.44 ha village is home to 26,083 residents, 44 percent of whom are of productive age (16–59 years). According to village government data, 425 MSME units are spread across five hamlets, predominantly in the trade, culinary, and garment sectors. This study adopts the Resource‑Based View (RBV), Endogenous Growth Theory, and Sustainable Rural Livelihoods Framework (SRLF) to examine the competitive advantages of MSMEs and the dynamics of village development. Employing a Participatory Action Research (PAR) methodology, the research includes situational analysis using GIS, service action planning, implementation of digital management training, and impact evaluation. Business management training, digital literacy workshops, and microfinance facilitation have been proven to enhance the capacity of MSME actors. The resulting “Local Resource‑Based MSME Potential” model is intended as an operational reference for village governments and partner institutions in designing more effective, inclusive, and sustainable economic empowerment programs